2022
DOI: 10.21873/cgp.20336
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning-based Analysis Identifies miRNA Expression Profile for Diagnosis and Prediction of Colorectal Cancer: A Preliminary Study

Abstract: Background: The stage of colorectal cancer (CRC) at the day of diagnosis has the greatest influence on survival rate. Thus, for CRC, which is mainly identified as advanced disease, non-invasive, molecular blood or stool tests could boost the diagnosis and lower mortality. Evaluation of miRNA expression levels in serum of patients diagnosed with CRC is a potential tool in early screening. Screening can be supported by machine learning (ML) as a tool for developing a cancer risk predictive model based on gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Hematological examinations have been reported as validated for the screening of CRC patients (23). Thus, we hypothesized that the serum level of CXCL10 reflects its expression in colorectal cancer tissues and tested this correlation.…”
Section: Discussionmentioning
confidence: 97%
“…Hematological examinations have been reported as validated for the screening of CRC patients (23). Thus, we hypothesized that the serum level of CXCL10 reflects its expression in colorectal cancer tissues and tested this correlation.…”
Section: Discussionmentioning
confidence: 97%
“… 32 Pawelka D et al found that a two-class Bayes Point Machine based on miRNA expression profiles has the potential to diagnose and prognosis. 33 Wan et al predicted early CRC using 2 classification methods (LR and SVM) and secured good results. 34 A comparison with existing models accentuates our model's cost-effectiveness utilizing routinely accessible blood indicators, while maintaining remarkable sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The EXIQON miRCURY LNA-based PCR platform (Qiagen, Hilden, Germany) was used to analyze the expression of 179 hsa-miRs in the serum samples of eight CRC subjects and ten controls [156]. Machine learning was used to develop a model for cancer risk prediction.…”
Section: Search For Mirna Markers For Crc Diagnosticsmentioning
confidence: 99%
“…A panel of 29 hsa-miRs upregulated in CRC was obtained; these miRNAs were regularly observable in the examined CRC samples. Repeated analysis of the publicly available hsa-miR profiles of CRC tumors or CRC exosomes demonstrated that two of the selected 29 hsa-miRs were upregulated in all datasets, hsa-miR-34a and hsa-miR-25-3p included [156].…”
Section: Search For Mirna Markers For Crc Diagnosticsmentioning
confidence: 99%